The performance of chemically and physically modified local kaolinite in methanol dehydration to dimethyl ether - Sanaa M. Solyman; Mohamed A. Betiha (Egyptian Journal of Petroleum)
The catalytic activity of modified natural kaolinite as a solid acid catalyst for dimethyl ether (DME) preparation was investigated by following up the conversion% of methanol and the yield% of DME. Natural kaolinite (KN) was treated chemically with H2O2 (KT) followed by thermal treatment at 500 °C (KC) and then mechano-chemically by ball milling with and without CaSO4 (KB-Ca and KB, respectively). These samples were characterized by XRD, FTIR, SEM, HRTEM, TGA and NH3-TPD techniques. The different techniques showed that the chemical treatment of kaolinite with H2O2 resulted in partial exfoliation/delamination of kaolinite, decreased the amount of acidic sites which is accompanied by increasing their strength. Calcination only decreased the acidic strength and slightly enlarged the particle size mostly due to heat effect. Ball milling resulted in multitude randomly-oriented crystals and increased the amount of acidic sites with the same strength of KT sample. CaSO4 mostly produced ordered monocrystalline kaolinite and created new acidic sites with slightly lower strength relative to KB. The catalytic activity and selectivity depend on the reaction temperature, the space velocity and the strength of acid sites. The most active sample is KB-Ca, which gives 84% DME due to its high amount and strength of acidic sites. The different modification methods resulted in 100% selectivity for DME.